2009
DOI: 10.1128/jvi.01797-08
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Extracellular Enveloped Virion Neutralization In Vitro and Protection In Vivo Depend on Complement

Abstract: Antibody neutralization is an important component of protective immunity against vaccinia virus (VACV).Two distinct virion forms, mature virion and enveloped virion (MV and EV, respectively), possess separate functions and nonoverlapping immunological properties. In this study we examined the mechanics of EV neutralization, focusing on EV protein B5 (also called B5R). We show that neutralization of EV is predominantly complement dependent. From a panel of high-affinity anti-B5 monoclonal antibodies (MAbs), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
171
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(192 citation statements)
references
References 100 publications
19
171
0
Order By: Relevance
“…The modest decrease in titer with the heat-inactivated serum was also previously observed with vaccinia virus (6). The relatively equivalent results after exposing EEV to either active or heat-inactivated serum establishes the resistance of the EEV form to complement-mediated neutralization in a second virus.…”
Section: Discussionsupporting
confidence: 55%
“…The modest decrease in titer with the heat-inactivated serum was also previously observed with vaccinia virus (6). The relatively equivalent results after exposing EEV to either active or heat-inactivated serum establishes the resistance of the EEV form to complement-mediated neutralization in a second virus.…”
Section: Discussionsupporting
confidence: 55%
“…Benhnia et al showed that monoclonal Abs (MAbs) specific for the EV protein B5 that are able to initiate complement-mediated lysis of infected cells and complement-dependent neutralization of EV particles in vitro provide better protection against VACV challenge following passive immunization (2,3). Furthermore, the enhanced protection provided by these MAbs in vivo was reduced when mice that had been passively immunized were depleted of complement prior to challenge, demonstrating that enhanced protection depended on the ability of MAbs to activate complement (3). Our data demonstrate that VCP limits the early nAb antibody response, but it is also likely that VCP reduces complement-mediated neutralization by nAbs that are produced.…”
Section: Discussionmentioning
confidence: 99%
“…For preparation of splenocytes as single-cell suspensions, spleens were manually homogenized on 40-m cell strainers into RPMI medium (Sigma). For preparation of peripheral blood leukocytes (PBL), blood was collected into EDTA-coated tubes, and erythrocytes were lysed by diluting whole blood in ACK buffer (0.15 M NH 4 Cl, 10 mM KHCO 3 , 0.1 mM EDTA) for 5 min. Splenocytes or PBL were washed thrice in PBS with 2% FBS prior to staining with cell-type-specific conjugated MAbs for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%